From pervasive chaos to evolutionary transition: The experience of healthcare providers during the COVID‐19 pandemic - Homeira Khoddam; Mahnaz Modanloo; Reza Mohammadi; Razieh Talebi (Wiley, 2024)
Abstract Aim The outbreak of the COVID‐19 pandemic confronted healthcare providers, especially physicians and nurses, with many unprecedented changes and physical and psychological pressures. This study aimed to explore the healthcare providers' experiences providing healthcare services for patients during the COVID‐19 pandemic in "Golestan, Northeast Iran". Design Qualitative, conventional content analysis. Methods A total of 13 eligible participants were recruited through the purposeful sampling method. Data were gathered using semi‐structured in‐depth individual interviews. Transcripts were analysed using an inductive content analysis based on the Elo and Kyngas model. The COREQ checklist was used to prepare the manuscript. Results The analysis of the data in this study led to the development of 16 subthemes and 5 themes emerged as follows pervasive chaos, imposed difficulties, paradoxical perceptions, committed efforts, and constructive transition. Conclusion The experience of HCPs during the COVID pandemic in "Iran" showed that despite the physical, mental, emotional, and social consequences, a kind of constructive evolution and transition has also taken place in personal, professional, and organizational dimensions. It is suggested that managers while strengthening and protecting the capabilities and skills that have emerged, to reduce the tensions of HCPs, have developed programs for comprehensive support from them in physical, psychological, social, and financial dimensions. Relevance to Clinical Practice It is necessary to improve inter‐professional cooperation, empathy, teamwork, professional commitment, and continuous learning in crises.